Post-operative infection and sepsis in humans is associated with deficient gene expression of Yc cytokines and their apoptosis mediators. - Ryan, Thomas; Doherty, Derek; Kelleher, Dermot; Mc Manus, Ross (My University, 2011)
INTRODUCTION: Lymphocyte homeostasis is dependent on the ?c cytokines. We hypothesised that sepsis in humans is associated with differential gene expression of the ?c cytokines and their associated apoptosis mediators. METHODS: The study population consisted of a total of 60 patients with severe sepsis, 15 with gram negative bacteraemia, 10 healthy controls and 60 patients undergoing elective lung resection surgery. Pneumonia was diagnosed by CDC NNIC criteria. Gene expression in peripheral blood leukocytes (PBLs) of interleukin (IL)-2, 7, 15 and interferon (IFN)-?, Bax, Bim, Bcl-2 was determined by qRT-PCR and IL-2 and IL-7 serum protein levels by ELISA. Gene expression of IL-2, 7 and IFN-? was measured in peripheral blood leukocytes (PBL), cultured in the presence of lipopolysacharide (LPS) and CD3 binding antibody (CD3ab) RESULTS: IL-2 gene expression was lower in the bacteraemia group compared with controls, and lower still in the sepsis group (P < 0.0001). IL-7 gene expression was similar in controls and bacteraemia, but lower in sepsis (P < 0.0001). IL-15 gene expression was similar in the three groups. Bcl-2 gene expression was less (P < 0.0001) and Bim gene expression was greater (P = 0.0003) in severe sepsis compared to bacteraemic and healthy controls. Bax gene expression was similar in the three groups.In lung resection surgery patients, post-operative pneumonia was associated with a perioperative decrease in IL-2 mRNA (P < 0.0001) and IL-7 mRNA (P = 0.003). IL-2 protein levels were reduced in sepsis and bacteraemia compared to controls (P = 0.02) but similar in pneumonia and non-pneumonia groups. IL-7 protein levels were similar in all groups.In cultured PBLs, IFN-? gene expression was decreased in response to LPS and increased in response to CD3ab with sepsis: IL-7 gene expression increased in response to LPS in controls and to CD3ab with sepsis; Bcl-2 gene expression decreased in response to combined CD3ab and IL-2 with sepsis. CONCLUSIONS: Patients with infection and sepsis have deficient IL-2 and IL-7 gene expression in PBLs. Aberrant cytokine gene expression may precede the onset of infection.
PUBLISHED
Keywords: Genetics; Infection; Immunology; Genes & Society; Immunology, Inflammation & Infection; International Development